Plan estratégico de marketing para la empresa de bloques hormipac. - Pauta Pullaguari, Wilson Hernán (2011)
The present work was developed with the purpose of contributing to the administrative management of the company of having prefabricated with the purpose of increasing its development and participation in the market of the construction, in order to elevate the level of sales and to maintain the competitiveness in what refers had prefabricated. The company of having prefabricated "HORMIPAC" from many years has participated in the development of the small industry of the city of Loja, it is one of the pioneers and one can say, the oldest in the County of Loja in what concerns to the elaboration of having prefabricated of concrete. The project STRATEGIC "PLAN DE MARKETING FOR THE COMPANY OF BLOCKS HORMIPAC", of the city of Loja, resides in the necessity of developing a strategic plan of marketing that impels the development and invigoration of the company object of the present study. The present project has been carried out based on theoretical sustenance‟s of Strategic Plans of Marketing and to field information obtained by means of the employment of surveys carried out in a total of 302 fixed clients, 7 employees and an interview to the Manager - proprietor. The objectives that thought about for the development of the present thesis work were: Capture new markets to increase sales and improve profits. Building the administrative organic structure of the company Hormipac, to make it more efficient and provide better customer service. Establish ongoing training seminars and motivation to all personnel of the company in order to conduct their activities efficiently. Create a dedicated office customer in order to know, needs, tastes and preferences. To elaborate a situational diagnosis of the environment so much Internal as External of the Company of blocks Hormipac, of the city of Loja. To carry out a market investigation identifying the influence area, the participation and the behavior of the company in the market of the city of Loja. To make an analysis FODA, identifying their main strengths, opportunities, weaknesses and threats. To propose strategies that you/they help to improve the production and the service in the factory of blocks Hormipac. To propose an improvement of the organic functional structure of the company of blocks Hormipac, with the purpose of having a better organization and yield. The strategic plan of marketing has a cost of $ 54.764.00 dollars the same ones that will be included in the budget of the year 2012 in the company HORMIPAC, for its setting in March and execution. Lastly you have ended up determining the conclusions and recommendations based on the study and carried out proposal. Having the direct responsibility for the implementation of this Strategic Plan from Marketing to the manager proprietor of the company Hormipac.